ANALYSIS OF THE RELATIONSHIP BETWEEN WATER QUALITY AWARENESS AND DRINKING WATER CONSUMPTION BEHAVIOR (CASE STUDY: MAJENE CITY AND CAMPALAGIAN VILLAGE, WEST SULAWESI) - Musafira, Musafira; Syahrir, Nur Hilal A.; Rahayu, Putri Indi (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2025)
The declining quality of drinking water sources due to contamination poses significant health risks, particularly in rural areas where public awareness about water quality and its impact on health is often limited. In Majene City and Campalagian Village, West Sulawesi, drinking water is predominantly sourced from wells and springs, but these sources have shown elevated levels of pollutants, such as manganese and coliforms, exceeding government standards. This study explores the relationship between water quality awareness and drinking water consumption behavior in these regions using Structural Equation Modeling-Partial Least Squares (SEM-PLS). Data were collected through household surveys and laboratory testing of water samples, focusing on physical, chemical, and biological parameters. SEM-PLS was employed for its ability to analyze latent variables and handle small sample sizes effectively. Results reveal that water quality awareness explains 78.6% of the variance in drinking water consumption behavior (R² = 0.786), with key indicators such as knowledge of water quality standards and contamination risks strongly predicting positive behavioral changes. Hypothesis testing confirmed a significant positive relationship (path coefficient = 0.887, p < 0.001), underscoring the importance of awareness in promoting healthy consumption behaviors. These findings highlight the need for targeted public education campaigns and policy interventions to improve water quality awareness and consumption practices. The study also contributes to the growing application of SEM-PLS in environmental and public health research, offering insights into the complex interplay between awareness and behavior. Future research should consider integrating socio-economic and cultural factors to develop a more holistic understanding of drinking water consumption patterns.